Gender Mainstream: Perspektif Khaled M. Aboe El Fadl: Gender Mainstreaming: The Perspective of Khaled M. Aboe El Fadl - Abdul Rokhim (Institute for Research and Community Service, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, East Java, Indonesia., 2011)
Obedience to the texts of the Qur'an and Hadith is a must for Muslims. In understanding the texts of the Qur'an and Hadith, Muslims sometimes act authoritarian towards what they understand from the texts. The practice of authoritarianism in Islamic legal studies is strongly opposed by Khaled M. Abou El Fadl. In this regard, Khaled M. Aboe El-Fadl has conducted extensive analysis of the texts in question, stipulating that the prerequisite for the authority of ijtihad must prioritize the following: honesty, sincerity, comprehensiveness, self-control, and rationality. For example, Khaled M. Aboe El Fadl, in addressing and responding to misogynistic hadiths, requires an analysis of the authoring process, because the hadiths that “slander” women and their establishment constitute a distortion of the historical facts of Islam in Medina. Ketaatan pada teks al-Qur'an dan al-Hadits adalah sebuah keharusan bagi umat Islam. Dalam memahami teks al-Qur'an dan al-hadits umat Islam kadang-kadang berbuat otoriter terhadap apa yang mereka pahami dari teks tersebut. Praktek otoritarianisme dalam kajian hukum Islam sangat ditentang oleh Khaled M. Abou El Fadl. Dalam hal ini Khaled M. Aboe El-Fadl banyak melakukan analisis terhadap teks-teks dimaksud dengan memberikan prasyarat keberwenangan umat berijtihad harus mengutamakan sikaр: kejujuran, kesungguhan, kemenyeluruhan, pengendalian diri dan rasionalitas.Misalnya, Khaled M. Aboe El Fadl dalam mensikapi dan menanggapi hadith-hadith misoginis dengan mengharuskan dilakukannya analisis persoalan tentang proses kepengarangan, sebab hadith-hadith